"It Gave Me My Life Back": An Evaluation of a Specialist Legal Domestic Abuse Service. (May 2016) - Lea, Susan J.; Callaghan, Lynne
Community-based advocacy services are important in enabling victims to escape domestic abuse and rebuild their lives. This study evaluated a domestic abuse service. Two phases of research were conducted following case-file analysis ( n = 86): surveys ( n = 22) and interviews ( n = 12) with victims, and interviews with key individuals ( n = 12) based in related statutory and community organizations. The findings revealed the holistic model of legal, practical, mental health–related, and advocacy components resulted in a range of benefits to victims and enhanced interagency partnership working. Core elements of a successful needs-led, victim-centered service could be distilled.